Detection Improvised Explosive Device (IED) Emplacement Using Infrared Image - Kamarul Hawari, Ghazali; M. S., Jadin (IEEE, 2014)
This paper presents a method to detect an improvised explosive device (IED) by using infrared thermography (IRT) technology. The detection of IED will be done automatically and accurately even the IED detection expert is not present. Combining the advantage of IRT and image processing technique, the proposed method is very efficient and responsive to detect the existence of hidden IED. The captured images are filtered and segmented to extract the heat pattern before the decision is made. Based on the experimental result, the proposed system produced about 92 % of detection accuracy.